THE VALUE OF 3-D IMAGING IN THE DIAGNOSIS AND PREOPERATIVE PLANNING OF FRACTURES OF THE ZYGOMATIC COMPLEX - Daniela Sulea; Alexandra Cracana; Victor-Vlad Costan; Eugenia Popescu (Romanian Society of Oral Rehabilitation, 2017)
Aim of the study Determining the importance of performing a three-dimensional CT reconstruction in the management of various fractures of the zygomatic complex, either isolated or in the context of associated facial fractures. Material and methods 31 cases of zygomatic complex fractures investigated by the use of computed tomography were reviewed regarding the diagnosis, preoperative planning and treatment. Results The 3D reconstruction was useful in determining the degree of comminution, the number, displacement and angulation of fragments as well as the relation with the surrounding tissues. This detailed understanding of the fracture pattern was beneficial in the assessment of the intraoperative situation. Conclusions The use of this technique is valuable in the accurate diagnosis of malar fractures, but also in deciding the appropriate treatment and approximating the amount of reduction needed in order to achieve symmetry of the zygomatic prominence and reconstruction of the facial contours.